Celestina. An annotated edition of the first Dutch translation (Antwerp,1550).Ed de Lieve Behiels y Kathleen V. Kish. Leuven University Press, Leuven, 2005 (Avisos de Flandes, Fuentes,1) Pornoboscodidascalus Latinus (1624). Kaspar Barth´s Neo-latin translation of Celestina. A critical ed. with introd., trs. and notes by Enrique Fernández.University of North Carolina Press at Chapel Hill, Valencia, 2006 (North Carolina Studies in the Romance Languages and Literatures, 284). - Alejandro Higashi (Nueva Revista de Filología Hispánica, 2010)
Se reseña los libros:Celestina. An annotated edition of the first Dutch translation (Antwerp, 1550) Pornoboscodidascalus Latinus (1624). Kaspar Barth´s Neo-latin translation of Celestina.